Assessing the impact of human capital development on economic growth in west African monetary zone: A pooled mean group estimation - Osobase, Petrolina Ebehiremen; Akanegbu, Benedict; Azu, Nnanna P. (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of human capital development on economic growth in the West African Monetary Zone (WAMZ) from 1990 to 2023, focusing on government expenditure on education and health. Grounded in the augmented Solow human capital growth model, the study applies the Autoregressive Distributed Lag (ARDL) estimation technique with the Pooled Mean Group (PMG) estimator to assess both short-run and long-run relationships. The findings indicate a positive and statistically significant long-run impact of education and health expenditure on economic growth, reinforcing the critical role of sustained human capital investments. However, short-run effects vary, with education expenditure contributing modestly to growth, while health expenditure shows a negative short-term impact, likely due to inefficiencies in resource allocation. The Error Correction Term (ECT) suggests that while some WAMZ economies adjust to equilibrium after economic shocks, others exhibit weak correction mechanisms. The causality analysis confirms that economic growth influences education expenditure, but the reverse relationship is not significant. These findings underscore the need for strategic, long-term investments in education and health and institutional reforms to maximize the economic benefits of human capital development in WAMZ countries.